UK health workers have key role in international disaster relief - Rokadiya, Sakib; Brown, Colin Stewart; O’Hara, Geraldine; McBride, Angela (BMJ (Online), 2015)
Sakib Rokadiya and colleagues highlight the important part played by NHS staff in the response to the Ebola epidemic in west Africa